2016
DOI: 10.1016/j.biortech.2016.02.052
|View full text |Cite
|
Sign up to set email alerts
|

GHG emission factors for bioelectricity, biomethane, and bioethanol quantified for 24 biomass substrates with consequential life-cycle assessment

Abstract: Document Version Peer reviewed version Link back to DTU Orbit Citation (APA):Tonini, D., Hamelin, L., Alvarado-Morales, M., & Astrup, T. F. (2016). GHG emission factors for bioelectricity, biomethane, and bioethanol quantified for 24 biomass substrates with consequential life-cycle assessment. Bioresource Technology, 208, 123-133. DOI: 10.1016/j.biortech.2016 AbstractGreenhouse gas (GHG) emission savings from biofuels dramatically depend upon the source of energy displaced and the effects induced outside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 18 publications
(19 reference statements)
2
63
0
2
Order By: Relevance
“…Qin et al (2018) stated that substituting fossil fuels with biofuels could also significantly reduce the air pollution (e.g., particulate matter) in China. Moreover, LCA studies have also demonstrated the environmental benefits of agro-residue based bioenergy production (Guerrero and Muñoz 2018; Soam et al 2017;Tonini et al 2016). Soam et al (2017) reported that the electricity production from rice straw produced a higher GHGs emission reduction than the traditional way in India.…”
Section: Life Cycle Environmental Impact Assessment Of Bioenergy Prodmentioning
confidence: 99%
See 1 more Smart Citation
“…Qin et al (2018) stated that substituting fossil fuels with biofuels could also significantly reduce the air pollution (e.g., particulate matter) in China. Moreover, LCA studies have also demonstrated the environmental benefits of agro-residue based bioenergy production (Guerrero and Muñoz 2018; Soam et al 2017;Tonini et al 2016). Soam et al (2017) reported that the electricity production from rice straw produced a higher GHGs emission reduction than the traditional way in India.…”
Section: Life Cycle Environmental Impact Assessment Of Bioenergy Prodmentioning
confidence: 99%
“…Soam et al (2017) reported that the electricity production from rice straw produced a higher GHGs emission reduction than the traditional way in India. Tonini et al (2016) reported that biofuel production from the agricultural residues without involving land use change is a promising emission reduction option from the perspective of life cycle. According to Parajuli et al (2017), cultivating willow and alfalfa as feedstocks for bioenergy can potentially sequestrate more soil organic carbon and thus lead to a lower carbon footprint.…”
Section: Life Cycle Environmental Impact Assessment Of Bioenergy Prodmentioning
confidence: 99%
“…If a fossil system is an alternative to using residues for energy production, the use of food waste for biofuel production can show overall negative GHG emission effect since the loss of energy will be compensated with fossil fuels. This relation will develop on the long-term as sources for the electricity and heat sector will be less pollutive for the environment [135].…”
Section: Environmental Governancementioning
confidence: 99%
“…Stąd przy rosnących celach redukcji GHG pojawia się konieczność prowadzenia obliczeń autentycznych wartości emisji GHG w cyklu życia biopaliw; w wielu przypadkach będą one dużo korzystniejsze niż wartość standardowa. Wartości liczbowe przedstawione w dyrektywie [14] i zobrazowane na rysunku 1 stanowią dane uśrednione, natomiast dane rzeczywiste, uzyskane w wyniku indywidualnych kalkulacji czy wyprowadzone dla różnych ścieżek, będą się znacząco między sobą różniły [13]. W Polsce dominującym surowcem do produkcji etanolu jest kukurydza [11].…”
Section: Składowe Emisji Ghg W Cyklu żYcia Bioetanoluunclassified